Irritable bowel syndrome leading to scurvy from a severely restricted diet. Issue 4 (1st October 2020) - Venkataraman, Vinayak; Olson, Kristian R.
Abstract: A 69-year-old man with irritable bowel syndrome on a restricted diet presented with fatigue, myalgias, extensive bilateral lower-extremity petechiae and ecchymoses, transfusion-refractory anemia, and elevated inflammatory markers. A low serum vitamin C level led to the diagnosis of scurvy. This is the first reported case of vitamin C deficiency and clinical scurvy related to voluntary dietary restriction from irritable bowel syndrome in an adult patient.